Player Experiences and Behaviors in a Multiplayer Game: designing game rules to change interdependent behavior - Niko Vegt; Valentijn Visch; Arnold Vermeeren; Huib de Ridder (Serious Games Society, 2016)
Serious gaming is used as a means for improving organizational teamwork, yet little is known about the effect of individual game elements constituting serious games. This paper presents a game design experiment aimed at generating knowledge on designing game elements for teamwork. In previous work, we suggested that interaction- and goal-driven rules could guide interdependence and teamwork strategies. Based on this finding, for the present experiment we developed two versions of multiplayer Breakout, varying in rule-sets, designed to elicit player strategies of either dependent competition or dependent cooperation. Results showed that the two rule-sets could generate distinct reported player experiences and observable distinct player behaviors that could be further discriminated into four patterns: expected patterns of helping and ignoring, and unexpected patterns of agreeing and obstructing. Classic game theory was applied to understand the four behavior patterns and made us conclude that goal-driven rules steered players towards competition and cooperation. Interaction rules, in contrast, mainly stimulated dependent competitive behavior, e.g. obstructing each other. Since different types of rules thus led to different player behavior, discriminating in game design between interaction- and goal-driven rules seems relevant. Moreover, our research showed that game theory proved to be useful for understanding goal-driven rules.